2017
DOI: 10.1108/jmd-10-2014-0134
|View full text |Cite
|
Sign up to set email alerts
|

The open source guild: creating more sustainable enterprise?

Abstract: Purpose-The purpose of this paper is to report on an action research project with two emergent micro-businesses that explored how their business model connected with the principles of open source. Design/methodology/approach-We first gained initial qualitative data to establish the core values of each micro-business, which we then explored in the context of open source and business models in two design workshops with each organisation. Findings-We developed the open source guild business model, which has the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The same applies to the disclosure of knowledge: Publicly releasing the collectively developed knowledge, such as source code (Dahlander & Magnusson, 2008; Henkel, 2006), technology and design blueprints (Troxler & Wolf, 2017), drug recipes (Pénin & Wack, 2008) or community energy project plans (Seyfang & Longhurst, 2016) attracts GOC members to projects. Again, from the perspective of PCs, researchers (Henkel, 2006; Larner et al, 2017; Martínez‐Torres et al, 2010) argue that the revealing should be selective to enable value capture and protect key intellectual property such as the business software version that a PC developed based on open‐source software. Pénin and Wack (2008) propose a patent‐like scheme that allows open access to collaboratively developed knowledge, thus providing a way to protect intellectual property while allowing others to continue working on the designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same applies to the disclosure of knowledge: Publicly releasing the collectively developed knowledge, such as source code (Dahlander & Magnusson, 2008; Henkel, 2006), technology and design blueprints (Troxler & Wolf, 2017), drug recipes (Pénin & Wack, 2008) or community energy project plans (Seyfang & Longhurst, 2016) attracts GOC members to projects. Again, from the perspective of PCs, researchers (Henkel, 2006; Larner et al, 2017; Martínez‐Torres et al, 2010) argue that the revealing should be selective to enable value capture and protect key intellectual property such as the business software version that a PC developed based on open‐source software. Pénin and Wack (2008) propose a patent‐like scheme that allows open access to collaboratively developed knowledge, thus providing a way to protect intellectual property while allowing others to continue working on the designs.…”
Section: Resultsmentioning
confidence: 99%
“…‘promoting shared values through a commons of experience and capturing value by protecting key intellectual property’ (Larner et al, 2017, p. 71)…”
Section: Methodsmentioning
confidence: 99%
“… 4. Similarly, it has been suggested that the Guild model provides examples of early quasi-social enterprise practice from as early as the ninth century (Defourny et al , 1999; Larner and Cheverst, 2017), but they existed in all of their various forms for the benefit of their members, rather than the wider community, and are therefore not addressed in this paper.…”
Section: Notesmentioning
confidence: 99%
“…During the author's engagement with founders and other stakeholders in the case study organizations, the open source guild business model (Larner, 2013) was offered as a starting point for discussion. In the open source guild model, the medieval guilds, as a preindustrial form of network organization (Deakin, 2006), are used as a metaphor, comparing the role of the software architect to the masters in the medieval guilds (Larner et al, 2017). In the case studies, the open source guild model acted as a design provocation (Bardzell and Bardzell, 2013), and also functioned as a boundary object (Star and Griesemer, 1989), by offering a new perspective on doing business which provoked reflection by both founders.…”
Section: Background To the Case Studiesmentioning
confidence: 99%